DESIGN AND IMPLEMENTATION OF A DATABASE SYSTEM FOR PSYCHOLOGICAL MONITORING OF MILITARY PERSONNEL IN LARGE ORGANIZATIONS (Modern education and development, 2025)
The psychological well-being of military personnel is a critical factor in maintaining national security and operational readiness. This study proposes the design and implementation of a database management system tailored for large organizations to monitor, evaluate, and manage the psychological condition of military service members. The database system enables structured storage, real-time access, and analysis of psychological test results, reports, and profiles. The research discusses data modeling, normalization, security, and integration with modern technologies. By automating psychological monitoring, organizations can take preventive measures and provide timely support to personnel in need.